(untitled) (Research, Society and Development, 2020)
Objective: to discuss the current production on the use of portable ultrasound in venous access in the critical neonate. Method: scoping review, based on the procedures recommended by experts from the Joanna Briggs Institute. In the first step of the methodology, the PCC framework was followed to identify the research question, with P being the type of population (newborn), C being the concept (use of portable ultrasound in central venous catheterizations), and C the context (neonatal intensive care unit). The following databases were consulted: SciELO, MEDLINE, accessed through the PubMed interface, and LILACS, accessed through the VHL. Google Scholar was used to access the grey literature and the research was made using the same descriptors used in the PubMed database, in conjunction with the Boolean operators “AND” and “OR”. The extraction of data and thematic discussion was carried out by all the authors, by consensus. Results: Of the three hundred and sixty-seven citations retrieved in the search, twenty-one articles, published between 2015 and 2020, were kept for the scoping review. Its contents were synthesized and discussed by thematic approach, with three categories emerging, one for each type of device found in the review: venous umbilical catheter; central venous catheter; peripherally inserted central catheter. Conclusion: The results obtained, even when limited by the small samples, support the use of point of care ultrasonography as the gold standard for the insertion and monitoring of these devices, adding quality and safety to procedures in critical neonates.